Effects of Canola Oil Consumption on Lipid Profile: A Systematic Review and Meta-Analysis of Randomized Controlled Clinical Trials. (17th February 2019) - Ghobadi, Saeed; Hassanzadeh-Rostami, Zahra; Mohammadian, Fatemeh; Zare, Morteza; Faghih, Shiva
Abstract: Hyperlipidemia is a well- known risk factor of cardiovascular disease. A healthy diet containing vegetable oils such as canola oil (CO) may help to reduce serum lipids. This study aimed to quantify the effects of CO on lipid parameters using a systematic review and meta-analysis of randomized controlled trials. PubMed, Web of Science, Scopus, ProQuest, and Embase were systematically searched until December 2017, with no time and design restrictions. Also, a manual search was performed to find extra relevant articles. Lipid parameters including total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), triglycerides (TG), apolipoprotein A1 (Apo A1), and apolipoprotein B (Apo B) were entered the meta-analysis. Weighed mean difference (WMD) and 95% confidence interval (CI) were stated as the effect size. Sensitivity analyses and prespecified subgroup were conducted to evaluate potential heterogeneity. Twenty-seven trials, comprising 1359 participants, met the eligibility criteria. Results of this study showed that CO consumption significantly reduced TC (−7.24 mg/dl, 95% CI, −12.1 to −2.7), and LDL (−6.4 mg/dl, 95% CI, −10.8 to −2), although it had no effects on HDL, TG, Apo B, and Apo A1. Effects of CO on TC and LDL significantly decreased after CO consumption in subgroups of >50 years of age participants and >30 intervention duration subgroup. Moreover, CO decreased LDL and TC compared to sunflower oil and saturated fat. This meta-analysis suggested that CO consumption improves serum TC and LDL, which could postpone heart disease progression. Key Teaching Points: CO consumption could decrease serum TC and LDL, although it had no effects on other blood lipids. There was an overall significant effect of canola oil on TC and LDL compared to sunflower oil and saturated fats. CO could have beneficial effects on serum TC and LDL just when consumed longer than 30 days. CO consumption improved lipid profiles in participants older than 50 years.